Inorganic all-solid-state electrochromic devices with reversible color change between yellow-green and emerald green. Issue 69 (31st July 2020) - Zhang, Xiang; Li, Wenjie; Chen, Xi; Zhao, Yingming; Wang, Lebin; Chen, Mingjun; Li, Zitong; Li, Yao
Abstract : All-solid-state ECDs prepared by evaporation exhibit bright color changes between yellow-green and emerald green. Abstract : All-solid-state electrochromic devices with the structure of glass/ITO/WO3 /Ta2 O5 /Li/V2 O5 /ITO were prepared by an evaporation method. Because of the use of a V2 O5 complementary layer, the ECD can achieve obvious color change between yellow-green and emerald green with superior cycling performance up to 5000 cycles, indicating the great potential in smart window applications.